Basic Skills for English Department Students Participating in the Kampus Mengajar Program: A Case Study in Universitas PGRI Yogyakarta - Rahmawan, Andi Dian; Dangin; Agustinus Hari Setiawan; Rudha Widagsa; Pramugara Robby Yana; Dery Tria Agustin (Universitas PGRI Yogyakarta, 2024)
This research seeks to reveal what basic skills are most needed by prospective students who will participate in one of the programs initiated by the Indonesian government, Kampus Mengajar. This can be a reflection of the study program where students are studying and preparing themselves, whether the material and training they have received before entering the field can be said to be sufficient, or whether there is still a lot of homework for the study program and students concerned to be more ready to handle school assistance tasks. By the government's initial goals and intentions, this program is designed to assist elementary, middle, and high school schools in improving literacy, numeracy skills, and mastery of learning technology for all students. This research was carried out by interviewing students who had completed Kampus Mengajar program at several schools. From the results of observations and in-depth interviews, it was discovered that the curriculum we implemented needed to be reviewed periodically to answer the school's challenges. Several things that deserve our attention as curriculum implementers are that there is a need to reduce courses that are linguistic theory in nature and increase the weight of learning that is training in nature in preparing learning models at the basic level.